2006
DOI: 10.1007/s11172-006-0368-y
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of α-pinene with tert-butyl hydroperoxide in the presence of Fe-pillared montmorillonite

Abstract: The reaction of α pinene with tert butyl hydroperoxide can proceed via allylic oxidation or α pinene isomerization, depending on the structural features of the catalysts based on Fe pillared montmorillonite.In spite of diversity of available methods for allylic oxidation of olefins, only few oxidation systems give α,β unsaturated alcohols or carbonyl compounds in ap propriate yields. Oxidation systems based on the lead(IV), selenium(IV), and chromium(VI) compounds turned out to be good in laboratory practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…In summary, FePcCl16-NH2-SiO2 is a stable and active catalyst for the allylic oxidation of [21] h a YVE: verbenone yield. b TBHP/α-pinene mol ratio = 4, 9 g/L catalyst.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In summary, FePcCl16-NH2-SiO2 is a stable and active catalyst for the allylic oxidation of [21] h a YVE: verbenone yield. b TBHP/α-pinene mol ratio = 4, 9 g/L catalyst.…”
Section: Discussionmentioning
confidence: 90%
“…Verbenone has been obtained using homogeneous and heterogeneous catalysts with moderate yields (Table 1) [14,15]; however, the requirement of expensive and toxic solvents [16][17][18][19], difficulty in catalyst recovery and product purification [20], inert atmosphere or large amount of catalyst and time, limit the application in some of those systems. Furthermore, in some cases reports do not include catalytic stability [21]. Hexadecachlorinated iron phthalocyanine immobilized on commercial silica FePcCl16-NH2-SiO2 (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Romanenko et al [76] found that the reaction of α-pyrene with tert-butyl hydroperoxide can proceed via allylic oxidation or α-pyrene isomerization, Scheme 11.6 Mechanism proposed for the cyclohexanone oxidation over synthetic Mg-saponite depending on the structural features of the catalysts based on Fe-PILC. After 50 h of reaction, Fe-PILC mainly gives isomerization products (limonene and camphene).…”
Section: Allylic Oxidationmentioning
confidence: 99%
“…-Scheme 1 -Up to now, various catalytic systems, either molecular complexes [16][17][18][19][20] or heterogeneous catalysts [21][22][23][24][25][26][27][28][29][30][31][32], have been used to produce verbenone. Nevertheless, in the most cases, low to medium yields were obtained ( Figure 1) or most of these processes still suffer from various drawbacks, such as sophisticated catalytic systems, toxic organic solvents and high amounts of oxidants, long reaction times, and difficult catalyst's recovery.…”
Section: Introductionmentioning
confidence: 99%